Determinants of Interest Using BSI Mobile Application: A Technology Acceptance Model Approach - Amalia Falasifah; Aulia Fuad Rahman; Yeney Widya Prihatiningtias (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: This study aims to analyze the determinants that influence interest in using BSI Mobile within the framework of the Theory of Acceptance Model. Methodology/approach: This research uses quantitative research methods. Determination of the sample with simple random sampling with the Slovin’s formula, namely 397 BSI KC Dharmawangsa Surabaya customers. Data collection techniques with questionnaires in the form of google forms. Data were analyzed using Partial Least Square (PLS) statistical techniques to test the relationship between variables. Findings: The results of this study indicate that perceived usefulness and perceived convenience have an effect on interest in using the BSI mobile application, but trust has no effect on interest in using the BSI mobile application. Financial literacy is able to moderate the effect of perceived usefulness, perceived convenience, and trust on interest in using the BSI mobile application at Bank Syariah Indonesia. Practical implications: The results of this study encourage Bank Syariah Indonesia to continue developing useful and easy-to-use features for the BSI Mobile app, as well as providing financial literacy education to customers. The government and financial services authorities are expected to improve digital financial literacy programs so that the public is better prepared and more confident in using technology-based banking services. Originality/value: This research has the novelty of financial literacy as a moderating variable using the theory of acceptance model.